1970
DOI: 10.3126/narj.v7i0.1860
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Varietal Evaluation of Rainy Season Tomato under Plastic House Condition

Abstract: Four tomato varieties namely LTH-61, Avinash-2, NSITH-162 and BL-410 were evaluated in farmer's field with farmers participation under plastic house condition for yield potential and other yield characters at Hemja, Kaski (920 masl) during rainy seasons of two consecutive years 2002 and 2003. The experiment was arranged in randomized complete block design with 5 replications, farmer as a replication. NSITH-162 took the shortest period of days to flowering and first harvest with an average of 36 and 66 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
5
17
0
Order By: Relevance
“…The present results are in agreement with the reports of various researches who found that growing tomatoes under protected structure during the rainy season reduced the incidence and severity of late blight by creating unfavorable environmental conditions for the infection, growth and development of the disease (Bowen and Kratky, 1982;Palada et al, 2003;Kratky, 2006;Pandey et al, 2006;Srinivasan, 2011;Wani et al, 2011;Kelley et al, 2014). In this regard, some…”
Section: Incidence and Severity Of Late Blightsupporting
confidence: 82%
“…The present results are in agreement with the reports of various researches who found that growing tomatoes under protected structure during the rainy season reduced the incidence and severity of late blight by creating unfavorable environmental conditions for the infection, growth and development of the disease (Bowen and Kratky, 1982;Palada et al, 2003;Kratky, 2006;Pandey et al, 2006;Srinivasan, 2011;Wani et al, 2011;Kelley et al, 2014). In this regard, some…”
Section: Incidence and Severity Of Late Blightsupporting
confidence: 82%
“…Though tomato is best suited to the Tarai, in low and mid hills, it is becoming increasingly attractive for cash generation in the high hills also (Pandey & Chaudhary 2004). Since, tomato supply from Tarai is constrained by high temperature, low fruit set, low flowering, bacterial wilt etc (Pandey et al 2006), tomato produced from mid June to November months in the hills (400-1800m) fetches higher market price ranging from Rs. 20 to Rs.…”
Section: Introductionmentioning
confidence: 99%
“…Srijana took the shortest period for flowering and harvesting with an average of 37 and 77 days after transplanting respectively. This was also the tallest variety with more clusters per plant [11,12].…”
Section: Literature Reviewmentioning
confidence: 87%
“…Pandey et al reported that the highest number of fruits (6.8) was produced by NSITH-162 whereas the lowest number of fruits (5.5) was produced by BL-410 [11]. The highest number of cluster (38.4) was produced by NSITH-162 whereas the lowest number of cluster (14.8) was produced by Avinash-2 among the four varieties Avinash-2, NSITH-162, LTH-61 and BL-410 [12][13][14].…”
Section: Literature Reviewmentioning
confidence: 99%